High-performance nanocrystalline soft magnetic composite material and preparation method thereof
Through sodium nitrate surface treatment and modified resin coating technology, the problem of poor heat resistance of soft magnetic composite materials during high-temperature heat treatment is solved, the resistivity and soft magnetic properties are improved, eddy current loss is reduced, and mechanical properties are enhanced.
Patent Information
- Application Number
- CN202411373697.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
AI Technical Summary
The existing soft magnetic composite materials have poor performance, especially poor heat resistance during high-temperature heat treatment.
The nanocrystalline alloy is surface-treated by sodium nitrate to form a passivation layer and coated with a modified resin composite material to form a dense insulating passivation film to improve resistivity and soft magnetic properties.
It improves the resistivity and soft magnetic properties of soft magnetic composite materials, reduces eddy current losses, enhances the thermal and chemical stability of the resin, and improves mechanical properties.
Smart Images

Figure CN119170370A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials, and specifically refers to a high-performance nanocrystalline soft magnetic composite material and a preparation method thereof. Background Art
[0002] Soft magnetic composite materials are magnetic composite materials prepared by powdering, insulating, bonding, rolling and heat treating soft magnetic metals. Due to their high saturation magnetic induction intensity, high magnetic permeability and low loss, they are widely used in the fields of electricity, electronics, communications and energy. The rapid development of information and communication technology in recent years has put forward higher requirements for soft magnetic composite materials. Applying amorphous nanocrystalline powder to soft magnetic composite materials can, on the one hand, give play to the advantages of high magnetic permeability of amorphous nanocrystalline soft magnetic alloys, which is conducive to obtaining large inductance and reducing winding and DC resistance; on the other hand, it can give play to the advantages of high resistivity of amorphous nanocrystalline soft magnetic alloys, which is conducive to reducing eddy current losses in powder particles and preparing ultra-high frequency soft magnetic composite materials. In practical applications, soft magnetic composite materials often need to be heat treated to eliminate the stress introduced during the pressing process, while epoxy resins and phenolic resins commonly used in traditional organic coating processes have poor heat resistance and are easily decomposed when heated, which limits the subsequent heat treatment temperature.
[0003] The existing technology currently has the following main problems: the performance of soft magnetic composite materials is poor. Summary of the invention
[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a high-performance nanocrystalline soft magnetic composite material and a preparation method thereof. In order to solve the above problems, the present invention proposes to perform surface treatment on the nanocrystalline alloy by sodium nitrate to generate a passivation layer on the surface to improve the performance of the soft magnetic composite material, and at the same time coat the modified resin composite material to protect the passivation layer while improving the resistivity and soft magnetic properties of the soft magnetic composite material.
[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a high-performance nanocrystalline soft magnetic composite material and a preparation method thereof, wherein the high-performance nanocrystalline soft magnetic composite material comprises the following components in parts by weight: 50-100 parts of FeSiBNbCu nanocrystalline alloy, 30-50 parts of sodium nitrate, and 18-35 parts of modified resin composite material.
[0006] Furthermore, the preparation method of the FeSiBNbCu nanocrystalline alloy comprises the following steps:
[0007] (1) using a vacuum tube furnace to anneal the FeSiBNbCu amorphous strip at a temperature of 550°C, a heating rate of 10°C / min, and holding for 10 min to obtain a nanocrystalline strip;
[0008] (2) The nanocrystalline ribbon described in step (1) is placed in a planetary ball mill, ball milled for 1-2 hours, and passed through a 200-mesh sieve to obtain a FeSiBNbCu nanocrystalline alloy.
[0009] Furthermore, in step (1), the composition weight ratio of the FeSiBNbCu amorphous strip is Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1 .
[0010] Furthermore, in step (2), the ball-to-material ratio of the ball mill is 20:1, and the rotation speed is 300 rpm.
[0011] Furthermore, the preparation method of the modified resin composite material comprises the following steps:
[0012] S1. Add nano-silica to 20 mL of anhydrous ethanol, stir for 10-20 min, add 4 mL of ammonia water and 2 mL of deionized water, stir for 30 min, add hexamethyldisilazane, react at 80° C. for 5-6 h to obtain modified nano-silica;
[0013] S2. Take epoxy resin and add it to 50 mL of acetone, add the modified nano-silica described in step S1, and stir for 20-30 minutes to obtain a modified resin composite material.
[0014] Furthermore, in step S1, the mass ratio of the nano-silicon dioxide to hexamethyldisilazane is 10:6-7.
[0015] Furthermore, in step S1, the mass fraction of the ammonia water is 25%.
[0016] Furthermore, in step S2, the mass ratio of the epoxy resin to the modified nano-silica is 5:2-3.
[0017] The present invention provides a method for preparing a high-performance nanocrystalline soft magnetic composite material, which specifically comprises the following steps:
[0018] ① Take sodium nitrate and add it to 30 mL of deionized water, adjust the pH value to 5, add FeSiBNbCu nanocrystalline alloy, stir at 25°C for 10 min, wash with anhydrous ethanol 3 times, and vacuum dry at 80°C for 8-12 h to obtain a modified nanocrystalline alloy;
[0019] ② Add the modified nanocrystalline alloy in step ① to the modified resin composite material, stir in a water bath at 45° C. for 1-2 h, place in a drying oven at 80° C. for 0.5 h, pass through a 125-mesh sieve, place in a mold and press at a pressure of 1200 MPa to form a magnetic ring with an outer diameter of 20 mm, an inner diameter of 12 mm, and a height of 5 mm;
[0020] ③ Place the magnetic ring described in step ② in a drying oven and heat it at 200°C for 2h, move it to a tubular furnace under argon atmosphere, heat it to 500°C at a rate of 5°C / min, keep it warm for 1h, and cool it to room temperature to obtain a high-performance nanocrystalline soft magnetic composite material.
[0021] The beneficial effects achieved by the present invention are as follows:
[0022] The invention performs surface treatment on a nanocrystalline alloy by sodium nitrate and coats a modified resin composite material, thereby improving the resistivity and soft magnetic properties of the soft magnetic composite material; performs surface passivation on a FeSiBNbCu nanocrystalline alloy by sodium nitrate to form a dense insulating passivation film with good coverage, thereby improving the resistivity of the nanocrystalline soft magnetic composite material, and simultaneously can hinder the conduction of eddy current between particles, thereby reducing the eddy current loss of the soft magnetic composite material; by grafting an alkane long chain to the surface of nano silicon dioxide, the content of surface hydroxyl groups is reduced, so that the surface contact angle is increased, thereby improving the dispersibility of the nano silicon dioxide; the modified nano silicon dioxide introduced into the modified resin composite material can not only improve the thermal stability of the resin, but also release the internal stress introduced during pressing to a greater extent during the annealing process, and can also improve the chemical stability of the resin, improve the mechanical properties of the soft magnetic composite material, and the addition of the modified nano silicon dioxide further improves the resistivity of the soft magnetic composite material; the modified resin composite material is coated on the outside of the insulating passivation film to improve the stability of the insulating passivation film, and the rupture and decomposition of the insulating passivation film are hindered during annealing, thereby improving the soft magnetic properties of the soft magnetic composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a graph showing the magnetic loss test results of high-performance nanocrystalline soft magnetic composite materials of Examples 1-3 of the present invention and Comparative Examples 1-2;
[0024] Figure 2 The resistivity test results of the high performance nanocrystalline soft magnetic composite materials of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown;
[0025] Figure 3 The coercivity test results of high-performance nanocrystalline soft magnetic composite materials of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in FIG.
[0026] Figure 4 This is a scanning electron microscope image of the high-performance nanocrystalline soft magnetic composite material described in Example 1 of the present invention.
[0027] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0030] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0031] Example 1
[0032] A high-performance nanocrystalline soft magnetic composite material comprises the following components in parts by weight: 50 parts of FeSiBNbCu nanocrystalline alloy, 30 parts of sodium nitrate and 18 parts of modified resin composite material.
[0033] Furthermore, the preparation method of the FeSiBNbCu nanocrystalline alloy comprises the following steps:
[0034] (1) using a vacuum tube furnace to anneal the FeSiBNbCu amorphous strip, wherein the weight ratio of the components of the FeSiBNbCu amorphous strip is Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1 , the temperature is 550°C, the heating rate is 10°C / min, and the temperature is kept for 10 minutes to obtain a nanocrystalline ribbon;
[0035] (2) The nanocrystalline ribbon described in step (1) was placed in a planetary ball mill and ball milled for 1 h at a ball-to-material ratio of 20:1 and a rotation speed of 300 rpm. The nanocrystalline ribbon was sieved through a 200-mesh sieve to obtain a FeSiBNbCu nanocrystalline alloy.
[0036] Furthermore, the preparation method of the modified resin composite material comprises the following steps:
[0037] S1. Take 1g of nano-silica and add it to 20mL of anhydrous ethanol, stir for 10min, add 4mL of 25% ammonia water and 2mL of deionized water, stir for 30min, add 0.6g of hexamethyldisilazane, react at 80℃ for 5h to obtain modified nano-silica;
[0038] S2. Take 5 g of epoxy resin and add it into 50 mL of acetone, add 2 g of the modified nano-silica described in step S1, and stir for 20 min to obtain a modified resin composite material.
[0039] This embodiment provides a method for preparing a high-performance nanocrystalline soft magnetic composite material, which specifically includes the following steps:
[0040] ① Add sodium nitrate to 30 mL of deionized water, adjust the pH value to 5, add FeSiBNbCu nanocrystalline alloy, stir at 25°C for 10 min, wash with anhydrous ethanol 3 times, and vacuum dry at 80°C for 8 h to obtain a modified nanocrystalline alloy;
[0041] ② Add the modified nanocrystalline alloy in step ① to the modified resin composite material, stir in a water bath at 45°C for 1 hour, place in a drying oven at 80°C for 0.5 hour, pass through a 125-mesh sieve, place in a mold under a pressure of 1200 MPa and press into a magnetic ring with an outer diameter of 20 mm, an inner diameter of 12 mm and a height of 5 mm;
[0042] ③ Place the magnetic ring described in step ② in a drying oven and heat it at 200°C for 2h, move it to a tubular furnace under argon atmosphere, heat it to 500°C at a rate of 5°C / min, keep it warm for 1h, and cool it to room temperature to obtain a high-performance nanocrystalline soft magnetic composite material.
[0043] Example 2
[0044] A high-performance nanocrystalline soft magnetic composite material comprises the following components in parts by weight: 100 parts of FeSiBNbCu nanocrystalline alloy, 50 parts of sodium nitrate and 35 parts of modified resin composite material.
[0045] Furthermore, the preparation method of the FeSiBNbCu nanocrystalline alloy comprises the following steps:
[0046] (1) using a vacuum tube furnace to anneal the FeSiBNbCu amorphous strip, wherein the weight ratio of the components of the FeSiBNbCu amorphous strip is Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1 , the temperature is 550°C, the heating rate is 10°C / min, and the temperature is kept for 10 minutes to obtain a nanocrystalline ribbon;
[0047] (2) The nanocrystalline ribbon described in step (1) was placed in a planetary ball mill and ball milled for 2 h at a ball-to-material ratio of 20:1 and a rotation speed of 300 rpm. The nanocrystalline ribbon was sieved through a 200-mesh sieve to obtain a FeSiBNbCu nanocrystalline alloy.
[0048] Furthermore, the preparation method of the modified resin composite material comprises the following steps:
[0049] S1. Take 1g of nano-silica and add it to 20mL of anhydrous ethanol, stir for 20min, add 4mL of 25% ammonia water and 2mL of deionized water, stir for 30min, add 0.7g of hexamethyldisilazane, react at 80℃ for 6h to obtain modified nano-silica;
[0050] S2. Take 5 g of epoxy resin and add it into 50 mL of acetone, add 3 g of the modified nano-silica described in step S1, and stir for 30 minutes to obtain a modified resin composite material.
[0051] This embodiment provides a method for preparing a high-performance nanocrystalline soft magnetic composite material, which specifically includes the following steps:
[0052] ① Sodium nitrate was added to 30 mL of deionized water, the pH value was adjusted to 5, and FeSiBNbCu nanocrystalline alloy was added. The mixture was stirred at 25°C for 10 min, washed with anhydrous ethanol for 3 times, and vacuum dried at 80°C for 12 h to obtain a modified nanocrystalline alloy.
[0053] ② Add the modified nanocrystalline alloy in step ① to the modified resin composite material, stir in a water bath at 45°C for 2h, place in a drying oven at 80°C for 0.5h, pass through a 125-mesh sieve, place in a mold and press at a pressure of 1200MPa to form a magnetic ring with an outer diameter of 20mm, an inner diameter of 12mm and a height of 5mm;
[0054] ③ Place the magnetic ring described in step ② in a drying oven and heat it at 200°C for 2h, move it to a tubular furnace under argon atmosphere, heat it to 500°C at a rate of 5°C / min, keep it warm for 1h, and cool it to room temperature to obtain a high-performance nanocrystalline soft magnetic composite material.
[0055] Example 3
[0056] A high-performance nanocrystalline soft magnetic composite material comprises the following components in parts by weight: 75 parts of FeSiBNbCu nanocrystalline alloy, 40 parts of sodium nitrate and 25 parts of modified resin composite material.
[0057] Furthermore, the preparation method of the FeSiBNbCu nanocrystalline alloy comprises the following steps:
[0058] (1) using a vacuum tube furnace to anneal the FeSiBNbCu amorphous strip, wherein the weight ratio of the components of the FeSiBNbCu amorphous strip is Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1, the temperature is 550°C, the heating rate is 10°C / min, and the temperature is kept for 10 minutes to obtain a nanocrystalline ribbon;
[0059] (2) The nanocrystalline ribbon described in step (1) was placed in a planetary ball mill and ball milled for 1.5 h at a ball-to-material ratio of 20:1 and a rotation speed of 300 rpm. The nanocrystalline ribbon was sieved through a 200-mesh sieve to obtain a FeSiBNbCu nanocrystalline alloy.
[0060] Furthermore, the preparation method of the modified resin composite material comprises the following steps:
[0061] S1. Take 1g of nano-silica and add it to 20mL of anhydrous ethanol, stir for 15min, add 4mL of 25% ammonia water and 2mL of deionized water, stir for 30min, add 0.65g of hexamethyldisilazane, react at 80℃ for 5.5h to obtain modified nano-silica;
[0062] S2. Take 5 g of epoxy resin and add it into 50 mL of acetone, add 2.5 g of the modified nano-silica described in step S1, and stir for 25 min to obtain a modified resin composite material.
[0063] This embodiment provides a method for preparing a high-performance nanocrystalline soft magnetic composite material, which specifically includes the following steps:
[0064] ① Add sodium nitrate to 30 mL of deionized water, adjust the pH value to 5, add FeSiBNbCu nanocrystalline alloy, stir at 25°C for 10 min, wash with anhydrous ethanol 3 times, and vacuum dry at 80°C for 10 h to obtain a modified nanocrystalline alloy;
[0065] ② Add the modified nanocrystalline alloy in step ① to the modified resin composite material, stir in a water bath at 45°C for 1.5h, place in a drying oven at 80°C for 0.5h, pass through a 125-mesh sieve, place in a mold under a pressure of 1200MPa and press into a magnetic ring with an outer diameter of 20mm, an inner diameter of 12mm and a height of 5mm;
[0066] ③ Place the magnetic ring described in step ② in a drying oven and heat it at 200°C for 2h, move it to a tubular furnace under argon atmosphere, heat it to 500°C at a rate of 5°C / min, keep it warm for 1h, and cool it to room temperature to obtain a high-performance nanocrystalline soft magnetic composite material.
[0067] Comparative Example 1
[0068] This comparative example provides a high-performance nanocrystalline soft magnetic composite material and a preparation method thereof, which differs from Example 1 in that sodium nitrate is not included in all components, the preparation steps do not include step ①, and the remaining components and component contents are the same as those in Example 1.
[0069] Comparative Example 2
[0070] This comparative example provides a high-performance nanocrystalline soft magnetic composite material and a preparation method thereof, which differs from Example 1 in that all components do not contain modified resin composite materials, the preparation steps do not include steps S1 and S2, and step ② directly presses the modified nanocrystalline alloy into a magnetic ring, and the remaining components and component contents are the same as those in Example 1.
[0071] Experimental example
[0072] 1. The high-performance nanocrystalline soft magnetic composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 were subjected to magnetic loss tests using a soft magnetic AC measuring instrument. The specific test parameters were: 20 turns of the primary coil, 20 turns of the secondary coil, a magnetic induction intensity of 50 mT, and a test frequency of 50 kHz-200 kHz.
[0073] 2. The resistivity of the high-performance nanocrystalline soft magnetic composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 was tested using a four-probe tester.
[0074] 3. The coercivity test of the high-performance nanocrystalline soft magnetic composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 was carried out using a soft magnetic DC measuring instrument. The specific test parameters were: 20 turns of the primary coil, 20 turns of the secondary coil, and an applied magnetic field of 1000 A / m.
[0075] 4. The surface morphology of the high-performance nanocrystalline soft magnetic composite material described in Example 1 was observed using a scanning electron microscope.
[0076] Results Analysis
[0077] Figure 1 This is a graph showing the magnetic loss test results of high-performance nanocrystalline soft magnetic composite materials of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, Example 1 has lower magnetic loss than Comparative Examples 1 and 2. This is because the surface of the magnetic powder is coated with a passivation film and a modified resin, which effectively blocks the contact between the particles. At the same time, the addition of nano-silicon dioxide further increases the resistivity and reduces the eddy current loss.
[0078] Figure 2 This is a graph showing the resistivity test results of high-performance nanocrystalline soft magnetic composite materials of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, the resistivities of Examples 1-3 are 84Ω·cm, 82Ω·cm, and 81Ω·cm, respectively, that of Comparative Example 1 is 59Ω·cm, and that of Comparative Example 2 is 48Ω·cm. Example 1 has a higher resistivity than those of Comparative Examples 1 and 2. This is because the coating layer has excellent insulation properties, which increases the resistance between the powder particles, thereby improving the resistivity of the soft magnetic composite material.
[0079] Figure 3This is a graph showing the coercive force test results of high-performance nanocrystalline soft magnetic composite materials of Examples 1-3 and Comparative Examples 1-2 of the present invention. As shown in the figure, the coercive forces of Examples 1-3 are 59 A / m, 61 A / m, and 63 A / m, respectively; Comparative Example 1 is 81 A / m; and Comparative Example 2 is 92 A / m. Example 1 has a lower coercive force than Comparative Examples 1 and 2.
[0080] Figure 4 This is a scanning electron microscope image of the high-performance nanocrystalline soft magnetic composite material described in Example 1 of the present invention. It can be seen that the powder surface has a well-uniform composite coating layer without obvious agglomerates. Since the modified resin composite material is attached to the surface, the roughness of the powder surface increases.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0082] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A high-performance nanocrystalline soft magnetic composite material, Features: The composition comprises the following components in parts by weight: 50-100 parts of FeSiBNbCu nanocrystalline alloy, 30-50 parts of sodium nitrate, and 18-35 parts of modified resin composite material.
2. A method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 1, Features: The specific steps include: ① Take sodium nitrate and add it to 30 mL of deionized water, adjust the pH value to 5, add FeSiBNbCu nanocrystalline alloy, stir at 25°C for 10 min, wash with anhydrous ethanol 3 times, and vacuum dry at 80°C for 8-12 h to obtain a modified nanocrystalline alloy; ② Add the modified nanocrystalline alloy in step ① to the modified resin composite material, stir in a water bath at 45° C. for 1-2 h, place in a drying oven at 80° C. for 0.5 h, pass through a 125-mesh sieve, place in a mold and press at a pressure of 1200 MPa to form a magnetic ring with an outer diameter of 20 mm, an inner diameter of 12 mm, and a height of 5 mm; ③ Place the magnetic ring described in step ② in a drying oven and heat it at 200°C for 2h, move it to a tubular furnace under argon atmosphere, heat it to 500°C at a rate of 5°C / min, keep it warm for 1h, and cool it to room temperature to obtain a high-performance nanocrystalline soft magnetic composite material.
3. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 2, Features: The preparation method of the FeSiBNbCu nanocrystalline alloy comprises the following steps: (1) using a vacuum tube furnace to anneal the FeSiBNbCu amorphous strip at a temperature of 550°C, a heating rate of 10°C / min, and holding for 10 min to obtain a nanocrystalline strip; (2) The nanocrystalline ribbon described in step (1) is placed in a planetary ball mill, ball milled for 1-2 hours, and passed through a 200-mesh sieve to obtain a FeSiBNbCu nanocrystalline alloy.
4. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 3, Features: In step (1), the composition weight ratio of the FeSiBNbCu amorphous strip is Fe 73.5 Si 13.5 B 9 Nb 3 Cu 1 .
5. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 4, Features: In step (2), the ball-to-material ratio of the ball mill is 20:1, and the rotation speed is 300 rpm.
6. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 5, Features: The preparation method of the modified resin composite material comprises the following steps: S1. Add nano-silica to 20 mL of anhydrous ethanol, stir for 10-20 min, add 4 mL of ammonia water and 2 mL of deionized water, stir for 30 min, add hexamethyldisilazane, react at 80° C. for 5-6 h to obtain modified nano-silica; S2. Take epoxy resin and add it to 50 mL of acetone, add the modified nano-silica described in step S1, and stir for 20-30 minutes to obtain a modified resin composite material.
7. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 6, Features: In step S1, the mass ratio of the nano-silicon dioxide to hexamethyldisilazane is 10:6-7.
8. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 7, Features: In step S1, the mass fraction of the ammonia water is 25%.
9. The method for preparing the high-performance nanocrystalline soft magnetic composite material according to claim 8, Features: In step S2, the mass ratio of the epoxy resin to the modified nano-silica is 5:2-3.
